2021
DOI: 10.30935/scimath/11381
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teaching Efficacy Belief and Attitude of Pre-service Teachers and Academic Achievement

Abstract: Given the importance of the beliefs and attitudes of the pre-service teachers, this research aims at studying the relation between mathematics teaching efficacy beliefs of pre-service teachers, their attitude towards mathematics and their mathematics academic achievement. Specifically, this work considers both factors together and studies their correlation with mathematics academic achievement. The Mathematics Teaching Efficacy Belief Instrument (MTEBI) is used to measure the teachers' efficacy beliefs of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…Attitudes have a stronger cognitive component than emotions and are relatively stable over time (Estrada & Batanero, 2020). Ruz et al (2021) found a positive association between content knowledge and attitudes of pre-service teachers, while Segarra and Julià (2022) also confirmed that teachers' efficacy beliefs as well as attitudes towards mathematics are key factors for pre-service teacher's mathematics academic achievement.…”
Section: Research Articlementioning
confidence: 70%
“…Attitudes have a stronger cognitive component than emotions and are relatively stable over time (Estrada & Batanero, 2020). Ruz et al (2021) found a positive association between content knowledge and attitudes of pre-service teachers, while Segarra and Julià (2022) also confirmed that teachers' efficacy beliefs as well as attitudes towards mathematics are key factors for pre-service teacher's mathematics academic achievement.…”
Section: Research Articlementioning
confidence: 70%
“…Several studies have addressed the psychological implications that the COVID-19 pandemic is having on students. As indicated by Garris and Fleck (2020), Bot (2021), Browning et al (2021), Daniels et al (2021), andSegarra andJulià (2022) several psychological factors, such as students' motivation, academic engagement, and perception of success, have decreased during the pandemic, while other factors, such as feelings of anxiety or cheating, have increased. According to these authors, each of these factors has a relationship with academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…One of the pillars of education is the teacher (Amir, 2019;Tantowi et al, 2022;Maher et al, 2022). In educational activities, teachers are critical actors in the progress of a country (Segarra & Julià, 2022). Teachers are expected to shape today's young generation's personality, character, morality, and intellectual capabilities (Singh et al, 2020;van Geel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%